Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\Leftrightarrow\left(x+3\right)\left(x+3-x+3\right)=0\Leftrightarrow x=-3\\ b,\Leftrightarrow x=0\left(x^2+4>0\right)\)
\(a,x^2+2.x.3+3^2-\left(x^2-3^2\right)=0\)
\(x^2+6x+9-x^2+9=0\)
\(6x+18=0\)
\(6x=-18\)
\(x=-3\)
Vậy x=-3
\(b,5x^3+20x=0\)
\(5x\left(x^2+4\right)=0\)
\(Th1:5x=0=>x=0\)
\(Th2:x^2+4=0\)
\(x^2=-4\)(vô lý)
Vậy x=0
a) \(\Rightarrow5x\left(x-200\right)-\left(x-200\right)=0\)
\(\Rightarrow\left(x-200\right)\left(5x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=200\\x=\dfrac{1}{5}\end{matrix}\right.\)
b) \(\Rightarrow x\left(x^2-11\right)=0\)
\(\Rightarrow x\left(x-\sqrt{11}\right)\left(x+\sqrt{11}\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=\sqrt{11}\\x=-\sqrt{11}\end{matrix}\right.\)
a) 5x(x-200)-(x-200)=0
(x-200)(5x-1)=0
Th1 : x-200=0
X=200
Th2 : 5x-1=0
5x=1
X=1/5
Vậy S={200;1/5}
\(\Rightarrow\left(x+3\right)\left(x+2\right)=0\Rightarrow\left[{}\begin{matrix}x+3=0\\x+2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-3\\x=-2\end{matrix}\right.\)
\(2\left(x+3\right)+x\left(3+x\right)=0\)
\(\Rightarrow\left(x+3\right)\left(x+2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-3\\x=-2\end{matrix}\right.\)
\(a,\Leftrightarrow\left(4x-8\right)\left(x+1\right)=0\\ \Leftrightarrow4\left(x-2\right)\left(x+1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\\ b,\Leftrightarrow\left(x+1\right)\left(x^2+1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-1\\x^2=-1\left(vô.lí\right)\end{matrix}\right.\Leftrightarrow x=-1\\ c,\Leftrightarrow x^2-2x-4x+8=0\\ \Leftrightarrow\left(x-2\right)\left(x-4\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=4\end{matrix}\right.\\ d,\Leftrightarrow x^3-3x^2+3x-9x+2x-6=0\\ \Leftrightarrow\left(x-3\right)\left(x^2+3x+2\right)=0\\ \Leftrightarrow\left(x-3\right)\left(x^2+x+2x+2\right)=0\\ \Leftrightarrow\left(x-3\right)\left(x+1\right)\left(x+2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=3\\x=-1\\x=-2\end{matrix}\right.\)
a) \(\Rightarrow4\left(x+1\right)\left(x-2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-1\\x=2\end{matrix}\right.\)
b) \(\Rightarrow x^2\left(x+1\right)+\left(x+1\right)=0\)
\(\Rightarrow\left(x+1\right)\left(x^2+1\right)=0\)
\(\Rightarrow x=-1\left(do.x^2+1\ge1>0\right)\)
c) \(\Rightarrow x\left(x-4\right)-2\left(x-4\right)=0\)
\(\Rightarrow\left(x-4\right)\left(x-2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=4\\x=2\end{matrix}\right.\)
d) \(\Rightarrow x^2\left(x-3\right)+3x\left(x-3\right)+2\left(x-3\right)\)
\(\Rightarrow\left(x-3\right)\left(x^2+3x+2\right)=0\)
\(\Rightarrow\left(x-3\right)\left(x+1\right)\left(x+2\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=3\\x=-2\\x=-1\end{matrix}\right.\)
a ,\(4x^2-\left(x-3\right)^2=0\)
\(\Leftrightarrow\left(2x-x+3\right)\left(2x+x-3\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(3x-3\right)=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x+3=0\\3x-3=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-3\\3x=3\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=-3\\x=1\end{matrix}\right.\)
Vậy
b,\(x^2-4+\left(x+2\right)^2=0\)
\(\Leftrightarrow\left(x^2-4\right)\left(x+2\right)^2=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+2\right)\left(x+2\right)^2=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=2\\x=-2\end{matrix}\right.\)
Vậy ...
\(a,x\left(x+5\right)-\left(x-2\right)\left(x+3\right)=0\\ \Leftrightarrow x^2+5x-x^2-x+6=0\Leftrightarrow4x=-6\\ \Leftrightarrow x=-\dfrac{3}{2}\)
\(b,2x^3-18x=0\\ \Leftrightarrow2x\left(x^2-9\right)=0\\ \Leftrightarrow2x\left(x-3\right)\left(x+3\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=3\\x=-3\end{matrix}\right.\)
a: Ta có: \(x\left(x+5\right)-\left(x-2\right)\left(x+3\right)=0\)
\(\Leftrightarrow x^2+5x-x^2-3x+2x+6=0\)
\(\Leftrightarrow7x=-6\)
hay \(x=-\dfrac{6}{7}\)
b: Ta có: \(2x^3-18x=0\)
\(\Leftrightarrow2x\left(x-3\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=3\\x=-3\end{matrix}\right.\)
Lời giải:
a. $x^2-100x=0$
$\Leftrightarrow x(x-100)=0$
$\Rightarrow x=0$ hoặc $x-100=0$
$\Leftrightarrow x=0$ hoặc $x=100$
b.
$x^2+5x+6=0$
$\Leftrightarrow (x^2+2x)+(3x+6)=0$
$\Leftrightarrow x(x+2)+3(x+2)=0$
$\Leftrightarrow (x+2)(x+3)=0$
$\Leftrightarrow x+2=0$ hoặc $x+3=0$
$\Leftrightarrow x=-2$ hoặc $x=-3$